2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5947458
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating alignments into Conditional Random Fields for grapheme to phoneme conversion

Abstract: Conditional Random Fields (CRFs) are a state-of-the-art approach to natural language processing tasks like grapheme-tophoneme (g2p) conversion which is used to produce pronunciations or pronunciation variants for almost all ASR pronunciation lexica. One drawback of CRFs is that for training, an alignment is needed between graphemes and phonemes, usually even 1-to-1. The quality of the g2p result heavily depends on this alignment. Since these alignments are usually not annotated within the corpora, external mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…CRF can handle overlapping context of features with a relative cohesion in an excellent way Apparently, to train CRF a training data with appropriate alignment and a template with details on the contextual frame size is required. One detriment in using CRF is the need of a monotonic alignment between the source and target symbol for resolving the one-to-many alignment [39]. This alignment process is not an integral part of a CRF and should be fabricated separately.…”
Section: Training Processmentioning
confidence: 99%
“…CRF can handle overlapping context of features with a relative cohesion in an excellent way Apparently, to train CRF a training data with appropriate alignment and a template with details on the contextual frame size is required. One detriment in using CRF is the need of a monotonic alignment between the source and target symbol for resolving the one-to-many alignment [39]. This alignment process is not an integral part of a CRF and should be fabricated separately.…”
Section: Training Processmentioning
confidence: 99%
“…Hidden Dynamic Conditional Random Fields [13] (HD-CRFs). In [14] it is shown that the computational cost for calculating a HCRF is not significantly changed compared to a CRF with given Alignment, as the numerator is a subset of the denominator. In the latter publication, the alignment is realized by adopting the BIO scheme [6], where the abbreviation stands for "begin" (B), "inside" (I), and "outside" (O) markers (cf.…”
Section: -To-n Alignmentsmentioning
confidence: 99%
“…In [10], a joint n-gram model is combined with a CRF model. In [11], many-to-1 alignment constraints are used with CRF models. However, in [12,7], many-to-many alignments are used.…”
Section: Introductionmentioning
confidence: 99%